Heterostructured bismuth vanadate multi-shell hollow spheres with high visible-light-driven photocatalytic activity. (February 2017) - Zong, Lingbo; Cui, Pengzhen; Qin, Feiyu; Zhao, Kun; Wang, Zumin; Yu, Ranbo
Graphical abstract: In this work, a modified carbonaceous spheres sacrificial template growth technique is developed to build up the Bi–V–O heterostructured multi-shell hollow shell composed of BiVO4 and Bi4 V2 O11 nanoparticles. These Bi–V–O hollow spheres demonstrate a high visible-light-driven photocatalytic activity towards the decomposition of Methylene blue. The Bi–V–O double-shell ones show the best photocatalytic activity due to the effective separation of photogenerated electrons and holes as well as the effective utilization of visible light induced by multiple reflections of their special multi-shell hollow structures. Highlights: Modified carbonaceous spheres sacrificial template approach. Controlling adsorption quantity of Bi 3+ and VO3 − ions in the carbonaceous microsphere templates and the heating process. Heterostructured Bi–V–O multi-shell hollow spheres. Effective separation of photogenerated electrons and holes as well as the effective utilization of visible light. Enhanced visible-light-driven photocatalytic activity towards the photodegradation of Methylene blue. Abstract: BiVO4 as one of the promising visible-light-driven photocatalysts attracted considerable research on morphology and composition control. In this work, a modified carbonaceous spheres sacrificial template growth technique are developed to build up multi-shell hollow spheres of the heterostructured Bi–V–O. By treating the carbonaceous spheres with NaOH aqueous, the simultaneous adsorption of Bi 3+ and VO3 − are achieved successfully, and through the precisely controlled calcination, the nanoparticles of BiVO4 and Bi4 V2 O11 are crystallized and interconnected into the Bi–V–O heterostructured multi-shell hollow spheres. These Bi–V–O hollow spheres demonstrate a high visible-light-driven photocatalytic activity towards the decomposition of Methylene blue, and the double-shell one with the highest Bi4 V2 O11 content shows the best photocatalytic activity. The high photocatalytic activity may due to the effective utilization of visible light induced by multiple reflections of their special multi-shell hollow spheres. The heterostructure between BiVO4 and Bi4 V2 O11 may also make a contribution to the enhanced photocatalytic activity.